2019
DOI: 10.1136/bmjoq-2019-000758
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional services for children in Beira, Mozambique: a study reporting on participatory use of data to generate quality improvement recommendations

Abstract: BackgroundExisting literature suggest frequent gaps in the quality of care (QoC) provided to children with malnutrition in low-income and middle-income countries. Beira is the second largest city in Mozambique. This study included two phases: phase 1 was a systematic assessment of the QoC provided to malnourished children in Beira; phase 2 aimed at using findings of the assessment to develop recommendations, with a participatory approach, to improve QoC.MethodsIn phase 1, all facilities offering nutritional ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…However, following major investments in prevention and control, HIV prevalence among children in Uganda is currently estimated to be relatively low (0.5%), 31 with an observed prevalence in malnourished children in West Nile Region of around 2.4%, 17 significantly lower than that reported in other nearby countries. 32 Additionally, studies have reported that the health status of refugees can be quite variable even within nearby areas, and volatile within a short time frame, due to multiple factors including population type and place of origin, local conditions like water and hygiene sanitation, existing protection services like distribution of food rations, and treatment services such as access to healthcare and availability of drugs and therapeutic foods. 2 4-7 The influence of all these factors on the final outcomes of refugee children with malnutrition should be better evaluated in future prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, following major investments in prevention and control, HIV prevalence among children in Uganda is currently estimated to be relatively low (0.5%), 31 with an observed prevalence in malnourished children in West Nile Region of around 2.4%, 17 significantly lower than that reported in other nearby countries. 32 Additionally, studies have reported that the health status of refugees can be quite variable even within nearby areas, and volatile within a short time frame, due to multiple factors including population type and place of origin, local conditions like water and hygiene sanitation, existing protection services like distribution of food rations, and treatment services such as access to healthcare and availability of drugs and therapeutic foods. 2 4-7 The influence of all these factors on the final outcomes of refugee children with malnutrition should be better evaluated in future prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other studies on nutrition in Mozambique, our results demonstrate that there are gaps in the Mozambican health system related to the availability and provision of items at health facilities required for adequate delivery of maternal and child nutrition interventions. [37][38][39] We also found that many health facilities offer maternal and child nutri- • Population with access to a health facility-refers to the population that lives within 10 kilometers of any health facility that is ready to deliver nutrition services.…”
Section: Discussionmentioning
confidence: 99%
“…CR is a proportion of patients successfully discharged as cured during the reporting period, of which discharges include cured, defaulters, deaths and non-respondents. Within Uganda, the CR in OTC is reported to be between 52.9% in Arua and 71.5% in Karamoja, 13 14 which is below the Sphere humanitarian standard of 75%. 15 …”
Section: Introductionmentioning
confidence: 95%
“…In Mozambique, CR among children with wasting managed in the health facilities was 48.2%. 13 CR among children managed in OTC in Ethiopia ranges from 61.8% to 79.6%. [17][18][19][20][21] Although CR in Karamoja improved in 2013-2016 (71.5%), 22 it was below the standard 75%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation